Clinical Profile and Short-Term Outcome of SARS-CoV-2-Infected Neonates from a Government Medical College in West Bengal, India. (19th January 2022) - Banerjee, Mukut; Pal, Jonaki; Mondal, Tanushree; Ghosh, Taraknath; Nayek, Kaustav
Abstract: Introduction: Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) has led to a terrifying global pandemic. The presentations in neonates are varied with less case severity compared to adults. Aim: To describe the clinical and laboratory features and outcomes of neonates admitted with SARS-CoV-2 infection during the second surge of COVID-19 pandemic in a Government Medical College, West Bengal, India. Materials and Methods: It is a hospital-based observational cross-sectional study conducted in the newborn unit of Burdwan Medical College and Hospital between 1 April 2021 and 31 July 2021 including all SARS-CoV-2 Real time RT-PCR (Reverse transcriptase polymerase chain reaction) positive neonates. The demographic, clinical and laboratory characteristics of all the neonates and their outcomes were documented and analysed. Results: Twenty-two neonates were found to be SARS-CoV-2 RT-PCR positive out of which 9 (40.9%) were found to be asymptomatic and 6 (27.27%) required neonatal intensive care unit admissions. Among the symptomatic neonates, most common presentations were respiratory distress (40.9%) and gastrointestinal manifestations (40.9%). Eight (36.36%) neonates required respiratory support. Three (13.6%) neonates had pneumonia of which one had right middle lobe collapse. Laboratory parameters were nonspecific except for the two (9%) cases of multisystem inflammatory syndrome in neonates. High-resolution computed tomography findings in two cases were suggestive of SARS-CoV-2 infection-induced changes. Two (9%) neonates died of which one was likely due to SARS-CoV-2 infection. Conclusion: Neonates with SARS-CoV-2 infection are mostly asymptomatic. However, clinicians must be vigilant as atypical presentations such as consolidation, collapse, meningitis or multisystem inflammatory syndrome may occur. Lay Summary: SARS-CoV-2 infection in neonates is rare with varied presentations ranging from asymptomatic neonates to a few presenting with multiorgan failure. The disease severity and case fatality are much less than in adults. We studied the clinical and laboratory features and outcomes of 22 neonates with SARS-CoV-2 infection during the second surge of COVID-19 pandemic. While nine (40.9%) neonates were asymptomatic, six (27.27%) required NICU admission. Pneumonia is a rare presentation in neonates but severe COVID-19 pneumonia resulting in consolidation and lobar collapse requiring positive pressure ventilation is a possibility. Multisystem inflammatory syndrome in neonates is also a clinical entity probably as a result of hyperinflammatory syndrome due to transplacental transfer of antibodies. They require rigorous treatment, close monitoring and regular follow-ups. Amniotic fluid, placental or cord blood testing is essential to ascertain the definite mode of transmission in these neonates.